Water column temperatures recorded during heat flow probe deployment, cruise PS134 - Caroline Brand; Norbert Kaul; Mareen Lösing; Karsten Gohl (PANGAEA, 2025)
Temperature profiles of the water column, extracted from Miniaturized Temperature Data-Logger (MTL) measurements collected during the deployment of the heat flow probe in the Bellingshausen Sea, cruise PS134. The depths were calculated from winch data and have an uncertainty of ~50 m.
In: Brand, C et al. (2025): Geothermal heat flow data collected during PS134 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984026